PEMANFAATAN APLIKASI CANVA SEBAGAI MEDIA PEMBELAJARAN MEMBUAT KOMIK STRIP MATERI TEKS ANEKDOT KELAS X-L SMA NEGERI 2 TARAKAN - Fathonah, Siti; A.R, Devi Amanda; Setyami, Inung (Smart Education, 2025)
Abstract: This article discusses the use of Canva as a learning aid to create comic strips in Indonesian language subjects on anecdotal text material. This study aims to determine the effectiveness of Canva as a creative learning medium that helps students understand the material in an interesting and interactive way. Through the use of Canva, students are invited to compose and visualize anecdotal texts in the form of comic strips, which are expected to increase their interest in learning and understanding of the material. The results of the study indicate that the Canva application can increase students' creativity and involvement in learning anecdotal texts. This study uses the Classroom Action Research (CAR) type of research. The subjects of the study were 35 students of class X-L of SMA Negeri 2 Tarakan. The data collection techniques used in this study were Interviews, Observations, and Documentation Studies. The difficulties of students in anecdotal text material are the lack of understanding of the structure and characteristics of anecdotal texts, difficulty identifying elements of humor and satire, especially if the context is related to social issues that they may be less familiar with. Students also have difficulty using short and concise language with appropriate vocabulary to convey messages, students find it difficult to adjust the right language to maintain a humorous or satirical nuance without reducing the message they want to convey. Therefore, there needs to be interesting media and learning methods to help students pour ideas and creativity into comic strips created using the Canva application. Keywords: student creativity, canva, anecdotal text, comic stripsAbstrak: Artikel ini membahas tentang penggunaan Canva sebagai alat bantu dalam pembelajaran untuk membuat komik strip dalam mata pelajaran Bahasa Indonesia pada materi teks anekdot. Penelitian ini bertujuan untuk mengetahui efektivitas Canva sebagai media pembelajaran kreatif yang membantu siswa memahami materi dengan cara yang menarik dan interaktif. Melalui penggunaan Canva, siswa diajak untuk menyusun dan memvisualisasikan teks anekdot dalam bentuk komik strip, yang diharapkan mampu meningkatkan minat belajar dan pemahaman mereka terhadap materi. Hasil penelitian menunjukkan bahwa aplikasi Canva dapat meningkatkan kreativitas dan keterlibatan siswa dalam pembelajaran teks anekdot. Penelitian ini menggunakan jenis penelitian kualitatif. Subjek penelitian adalah siswa kelas X-L SMA Negeri 2 Tarakan yang berjumlah 35 siswa. Teknik pengumpulan data yang digunakan pada penelitian ini adalah Wawancara, Observasi, dan Studi Dokumentasi. Adapun kesulitan siswa pada materi teks anekdot adalah kurangnya pemahaman struktur dan ciri teks anekdot, kesulitan mengidentifikasi unsur humor dan sindirihan terutama jika konteksnya berhubungan dengan isu-isu sosial yang mungkin kurang mareka kenal. Siswa juga kesulitan menggunakan bahasa yang singkat dan padat dengan kosakata yang sesuai untuk menyampaikan pesan, siswa merasa sulit menyesuaikan bahasa yang tepat agar tetap memiliki nuansa humor atau sindiran tanpa mengurangi peswan yang ingin disampaikan. Oleh sebab itu, perlu adanya media dan metode pembelajaran yang menarik agar dapat membantu siswa dalam menuangkan ide dan kreativitas ke dalam komik strip yang dibuat menggunakan aplikasi Canva.Kata kunci: kreativitas siswa, canva, teks anekdot, komik strip